Hope in the face of death - Hanhart, Karel (Neotestamentica, 1997)
The adoption of the minority reading (2 Cor 5:3) in Nestle-Aland28 is unwarranted because the copyist assumed Paul knew the open tomb tradition and had taken a disappearance of Jesus' dead body literally. To him Paul would have feared to die before the parousia and thus enter a state of a 'naked', disembodied soul, Paul rather reckoned with appearing before Christ's judgment seat when mortals might appear 'naked' in shame. He nowhere shows a knowledge of the open tomb tradition. Moreover, the majority reading fits hand in glove with Paul's imagery in 2 Cor 4: 16-5: 1 0 and his soteriology elsewhere. The open tomb story should be read as a midrashic aggadah.